Financial Inclusion and the Success of MSMEs - Sri Rahayu (Universitas Pendidikan Ganesha, 2022)
The inability to access financial services can have a major impact on the sustainability and success of business actors. Financial inclusion is expected to be maximized so that business actors can be assisted in achieving business success. Currently, business actors based on creative and non-creative economics are the largest business actors in Sumbawa Regency, reaching 11,598 business units consisting of 11,347 micro businesses, 244 small businesses and 7 medium businesses. The results of this study indicate that in the development of economic in Sumbawa Regency, it is recognized that most micro business actors are still facing various problems. Lack of market access, capital, development of information technology and development of human resources, business networks, resulting in low productivity and competitiveness of business actors. However, some business actors have started to rise because they received assistance from the government in the National Economic Recovery scheme.